Technical-economical assessment of solar PV systems on small-scale fishing vessels - I Made Aditya Nugraha; Febi Luthfiani; Grangsang Sotyaramadhani; Aris Widagdo; I Gusti Made Ngurah Desnanjaya (Institute of Advanced Engineering and Science, 2022)
The source of lighting in ships can be sourced from electrical energy generated by using generators or now can utilize new renewable energy, such as solar energy using PV. Based on the existing potential, Indonesia has good solar energy potential. The measurement results show that the potential for solar energy reaches 6.37 kWh/m2/day. This potential can certainly be utilized in the marine and fisheries world. The utilization of PV as a source of electrical energy on fishing boats is expected to help support government policies in terms of the blue economy and overcome the limited number of fossil energy sources. In this study, the installation of PV with a size of 100 WP was installed on fishing boats. The need for electrical energy for PV energy output shows that it can meet 50.52% of electrical energy needs. This result is supported by the Wilcoxon test that electrical energy needs can be met by PV with a p < 0.005. The results of the economic analysis also show that the use of solar energy as a source of electrical energy provides an IRR of 9%, with a payback period of 8.87 years.